Reproductive decisions after the diagnosis of amniotic fluid embolism. (April 2017) - Moaddab, Amirhossein; Klassen, Miranda; Priester, Cynthia D.; Munoz, Elvira H.; Belfort, Michael A.; Clark, Steven L.; Dildy, Gary A.
Abstract: Objective: This study aims to describe the subsequent reproductive outcomes in women who either correctly or incorrectly were diagnosed with amniotic fluid embolism (AFE). Study design: Medical records were obtained, abstracted and reviewed by authors with extensive experience in critical care obstetrics. Telephone interviews of all survivors were conducted to determine obstetrical and contraceptive history. A subgroup underwent further telephone interview to address subsequent reproductive decisions. Results: By November 2015, 116 medical records of patients diagnosed with AFE were reviewed. Patients who had undergone hysterectomy (n = 26), died (n = 9), or developed Sheehan's syndrome (n = 1) at the time of the original event were excluded from the present analysis. Of the remaining 80 women, 30% (24/80) had subsequently conceived and 32.5% (26/80) patients or their partners had undergone permanent sterilization. At the time of this report, 66% (21/32) of registry participants were categorized to have had AFE and 34% (11/32) as not likely AFE or indeterminate. Conclusions: The syndrome of AFE is over-diagnosed. Women diagnosed with AFE who survive conceive another pregnancy less frequently than US women over similar time intervals and often choose a permanent sterilization method, whether or not they actually had AFE, largely out of fear of AFE recurrence.